Pengaruh Price Earning Ratio (PER) terhadap Harga Saham Syariah pada Bank Syariah Indonesia - Sevira Eka Putri; Rini Elvira (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This research aims to determine the impact of the Price Earnings Ratio (PER) on the Sharia share price of Bank Syariah Indonesia (BSI). The Sharia share price refers to the price set by a company for shares in line with Islamic principles. Many factors influence share prices, with the PER being a key fundamental variable. The study employs a quantitative approach, utilizing secondary data from the Indonesia Stock Exchange and financial reports of BSI from 2019 to 2024, with a sample size of N=71. The analysis involves normality, homogeneity, and linearity tests, along with hypothesis testing (t-test), simple linear regression, and the Adjusted R-Squared Test. The findings indicate that the PER significantly affects the Sharia share price (Y), with a significance value of 0.000 (p < 0.05) and a t-count of 4.554, which exceeds the t-table value of 1.690, suggesting a positive and significant relationship. The R-Squared value is 0.372, meaning the PER explains 37.2% of the variation in share prices, with the remaining 62.8% influenced by other factors not covered in this research, such as EPS, PBV, and others.